PARAMETRIC STUDY OF WARREN STEEL TRUSS BRIDGE USING ARTIFICIAL NEURAL NETWORKS - Astuti, Yana; Priyosulistyo, Henricus; Triwiyono, Andreas; Aminullah , Akhmad (Himpunan Pengembangan Jalan Indonesia (HPJI), 2025)
Abstract Steel truss bridges are a popular type of amongst several other standard bridges in Indonesia due to their lightweight yet robust and strong structure. In this study Artificial Neural Networks is used to optimize the dimensions of the steel truss bridge. The Artificial Neural Network method was chosen as it can handle complex and nonlinear problems, as well as its potential to generate accurate prediction models. Data of 319 existing constructed steel truss bridges in Indonesia were used to train the Artificial Neural Network model. The results show that the Artificial Neural Network model can predict the stress ratio of the structural elements of steel truss bridges with high accuracy (R2 > 0.99). The trained ANN model was then used to optimize the dimensions of the steel truss bridges with spans range from 40 meters to 60 meters with interval of 5 meters. The optimization results showed a 5.60% weight reduction compared to previous research results and a 20% less compared to the average weight of the existing bridge. This study contributes to improving the efficiency of development steel truss bridge in Indonesia. Keywords: truss bridge; optimization; Artificial Neural Network; design efficiency Abstrak Jembatan rangka baja merupakan jenis jembatan standar yang populer di Indonesia karena struktur yang ringan namun kuat dan kokoh. Pada penelitian ini, Artificial Neural Network digunakan untuk mengoptimalkan dimensi jembatan rangka baja. Metode ini dipilih karena kemampuannya menangani masalah kompleks dan nonlinier, serta potensinya untuk menghasilkan model prediksi yang akurat. Data 319 jembatan rangka baja yang ada di Indonesia digunakan untuk melatih model Artificial Neural Network. Hasilnya menunjukkan bahwa model Artificial Neural Network dapat memprediksi rasio tegangan pada elemen struktural jembatan rangka baja dengan akurasi yang tinggi. Model Artificial Neural Network yang terlatih kemudian digunakan untuk mengoptimalkan dimensi jembatan rangka baja dengan rentang bentang 40 meter hingga 60 meter dengan interval 5 meter. Hasil optimasi menunjukkan efisiensi berat sebesar 5,60% dibandingkan dengan penelitian sebelumnya dan 20% lebih efisien dibandingkan dengan jembatan yang sudah ada. Penelitian ini berkontribusi dalam meningkatkan efisiensi pengembangan jembatan rangka baja di Indonesia. Kata-kata kunci: jembatan rangka baja; optimasi; Artificial Neural Network; efisiensi desain